Time-Inconsistent Preferences and Social Security - Imrohoroglu, A.; Imrohoroglu, S.; Joines, D. H. (Quarterly Journal of Economics, 2003)
In this paper we examine the role of social security in an economy populated by overlapping generations of individuals with time-inconsistent preferences who face mortality risk, individual income risk, and borrowing constraints. We find that unfunded social security lowers the capital stock, output, and consumption for consumers with time-consistent or time-inconsistent preferences. However, it may raise or lower welfare depending on the strength of time inconsistency.